SOCIAL MEDIA AND COMMERCE: A REVIEW OF THE INDONESIAN GOVERNMENT'S EFFORTS TO REGULATE ONLINE TRANSACTIONS - Archristhea Amahoru; Abdurrahman Sadikin; Firman Aziz; Egidius Fkun; Ismail Ludin (Sean Institute, 2023)
The present study undertakes an examination of the impact that social media and e-commerce have on regulation by the Indonesian government. E-commerce is expanding at an exponential rate, while social media platforms such as Facebook and Instagram have become vital marketing tools due to the proliferation of smartphones and increasing internet penetration. This article scrutinizes pertinent regulations aimed at safeguarding consumer rights and regulating online transactions, such as the ITE Law and regulations issued by the Minister of Communication and Information Technology. Particular attention is paid to the difficulties encountered during the enforcement and compliance phases of implementing these regulations. The discourse also encompasses the obstacles and advantages encountered by micro, small, and medium enterprises (MSMEs) in the digital economy, underscoring the criticality of government assistance and digital education in facilitating their migration to online markets. The study's findings indicate that although e-commerce and social media present substantial prospects for economic expansion, Indonesia must maintain a steadfast commitment to consumer protection and efficient regulatory measures in order to guarantee development that is both inclusive and sustainable.